Pop-Up Book Learning Media for Understanding Early Childhood Sexual Education for the 5-6-Year-Old Age Group - Kadek Ina Anggasari; Made Vina Arie Paramita; Rendy Setyowahyudi (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The public thinks that sex education is not appropriate to be given to young children. Padahal pendidikan seks yang diberikan sejak dini sangat berpengaruh dalam kehidupan anak ketika dia memasuki masa remaja. Sex education can be introduced to early childhood by utilizing learning media using pop-up books. This research aims to develop learning media in the form of pop-up books that contain sex education for early childhood. The research model used is the ADDIE model. Data collection is carried out by observation and validation questionnaires to obtain expert assessments from media experts, material experts, and practitioners. The results of the validation of the pop-up book on media experts obtained a percentage of 4.5 with the category of very feasible, and the validation of material experts obtained a percentage of 5 with the category of very feasible, and the validation of media feasibility by teachers obtained a percentage of 4.6 with the category of feasible. Based on the results of the validation of media experts and material experts, as well as practitioners, it can be concluded that the pop-up book media developed is very feasible to be used as a learning medium in introducing sex education in early childhood. The implication of this study is the creation of Pop-up Book learning media to improve the understanding of early childhood sexual education in the age group of 5-6 years.